A mannose-specific C-type lectin from Fenneropenaeus merguiensis exhibited antimicrobial activity to mediate shrimp innate immunity. (December 2017) - Runsaeng, Phanthipha; Puengyam, Peerapong; Utarabhand, Prapaporn
Highlights: FmLC3 is a C-type lectin produced in F. merguiensis hepatopancreas. Native FmLC3 protein was found in some tissues unless hepatopancreas. FmLC3 transcription was up-regulated after bacterial and viral challenge. rFmLC3 exhibits binding and agglutinating activity with Ca 2+ -dependence. rFmLC3 promotes diverse microbial growth inhibition in a dose-dependence. Abstract: Being one type of pattern recognition receptors (PRRs), lectins exhibit a crucial role in the defense mechanism of invertebrates which are deficient in an adaptive immune system. A new C-type lectin called FmLC3 was isolated from hepatopancreas of Fenneropenaeus merguiensis by cloning approaches, RT-PCR and 5′ and 3′ RACE (rapid amplification of cDNA ends). A full-length cDNA of FmLC3 contains 607 bp with one open reading frame of 480 bp, encoding a 159-amino acids peptide. The predicted primary structure of FmLC3 is composed of a signal peptide, a carbohydrate recognition domain with an EPN motif and one Ca 2+ binding site-2, including a double-loop region assisted by two conserved disulfide linkages. FmLC3 had a molecular mass of 17.96 kDa and pI of 4.92. In normal or unchallenged shrimp, the mRNA expression of FmLC3 was detected only in hepatopancreas whilst its native proteins were found in hemolymph, heart, stomach and intestine but not in the expressed tissue, indicating that after being synthesized in hepatopancreas, FmLC3 would be secreted to other tissues. The significant up-regulation of FmLC3 was manifested in shrimp challenged with Vibrio harveyi or white spot syndrome virus. After knockdown with gene-specific double-stranded RNA and following by co-pathogenic inoculation, the FmLC3 expression was severely suppressed with coherence of increasing in cumulative mortality and reduction of the median lethal time. Recombinant FmLC3 (rFmLC3) had agglutinating activity towards diverse bacterial strains in a Ca 2+ -dependent manner. Its activity was inhibited by lipopolysaccharide and mannose, implying that FmLC3 was mannose-binding C-type lectin. Moreover, rFmLC3 could bind directly to various microbial strains with Ca 2+ -requirement. Otherwise, rFmLC3 exhibited the antimicrobial activity by inhibiting effectively the microbial growth in vitro . All these results signified that FmLC3 might act as PRR to recognize with a broad specificity for diverse pathogens, and contribute in shrimp immune response via the agglutination, binding and antimicrobial activity.